1997
DOI: 10.1016/s0030-4018(96)00720-1
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime quenching in Yb-doped fibres

Abstract: We have discovered that in ytterbium-doped silica fibres the excited state lifetime of a fraction of the Yb ions can be quenched to a very small value, leading to a strong unbleachable loss. This unexpected behaviour seems to be caused by some, yet unidentified, impurity or structural defect. It is of considerable relevance for various Yb doped lasers and amplifiers including Er:Yb codoped fibres as used in telecommunication amplifiers although it should also be emphasized that fibres can be produced that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
91
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(101 citation statements)
references
References 3 publications
10
91
0
Order By: Relevance
“…The fiber with lower Yb concentration ( m ) exhibited an unsaturable loss 2 3 m (13 dB/m), whereas in the fiber with large Yb concentration ( m ), this value was as large as 30 m (130 dB/m). The unsaturable loss phenomenon in Yb-only-doped media has been reported previously [10], [27], [28]. Although the exact mechanism behind this absorption has not yet been explained, the overall effect appears to be due to lifetime quenching of a portion of Yb ions.…”
Section: Spectroscopy At Pump Wavelengthmentioning
confidence: 66%
See 3 more Smart Citations
“…The fiber with lower Yb concentration ( m ) exhibited an unsaturable loss 2 3 m (13 dB/m), whereas in the fiber with large Yb concentration ( m ), this value was as large as 30 m (130 dB/m). The unsaturable loss phenomenon in Yb-only-doped media has been reported previously [10], [27], [28]. Although the exact mechanism behind this absorption has not yet been explained, the overall effect appears to be due to lifetime quenching of a portion of Yb ions.…”
Section: Spectroscopy At Pump Wavelengthmentioning
confidence: 66%
“…Around this wavelength, the Yb absorption is largest, which leads to the maximum energy transfer from pump to signal over the shortest length. The total pump absorption coefficient by both Yb and Er ions is given by (10) where is the overlap coefficient between the pump power distribution and the active medium cross section. stands for any constant background loss at the pump wavelength.…”
Section: Spectroscopy At Pump Wavelengthmentioning
confidence: 99%
See 2 more Smart Citations
“…5.1 show the pump absorption versus launched pump power of the waveguide with an Er A number of authors [109][110][111][112][113] have attributed a similar behavior observed in other host materials to a fast quenching process. In our samples, such a process can be induced by, e.g., fast static ETU due to active ion pairs or clusters, energy transfer to undesired impurities, or trapping of excitation energy by host material defects, such as voids.…”
Section: +mentioning
confidence: 67%